2002
DOI: 10.1002/jbm.10218
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of osteoblastic cells contacted by orthopedic implant particles

Abstract: Particles generated from orthopedic implants through years of wear play an essential role in the aseptic loosening of a prosthesis. We have investigated the biocompatibility of these orthopedic particles on different osteoblast-like cells representative of different stages of osteoblast maturation. We found the particles induced a caspasedependent apoptosis of osteoblasts, with less mature osteoblasts being the most susceptible. An analysis of gene expression was performed on the less mature osteoblasts, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 33 publications
2
44
1
Order By: Relevance
“…[56][57][58] To address whether this may be true in vivo, we performed expression analysis on two key regulators of osteogenesis, BMP4 and FGF18. FGF18 has been reported to promote osteogenesis and osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58] To address whether this may be true in vivo, we performed expression analysis on two key regulators of osteogenesis, BMP4 and FGF18. FGF18 has been reported to promote osteogenesis and osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to have a comprehensive description of the cell-implant interaction with surface treated Ti alloy, cDNA microarray technology may be performed e.g. [34,35]. This represents the next step of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, combination of particles and cytokines had a synergic effect on the production of inflammatory factors [13]. Using microarray techniques, it has been shown that particles had a profound impact on genes coding for inflammatory cytokines and genes controlling the nuclear architecture [14]. Nevertheless, little information is available regarding the effect of particles on osteoclastogenetic factors produced by osteoblasts.…”
Section: Introductionmentioning
confidence: 99%